Implementasi Model Pembelajaran Creative Problem Solving (CPS) Untuk Meningkatkan Kemampuan Berpikir Kreatif Siswa - Prasella, Ananda Dea Prasella; Susantiningrum Susantiningrum; Winarno Winarno (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2023)
This research aims to determine the improvement of students' creative thinking ability through the implementation of the Creative Problem Solving (CPS) learning model in the Element 10 of Public Relations and Protocol Management for grade XI MPLB students at SMK N 1 Sukoharjo. This research is a classroom action research, conducted over two cycles. Each cycle is carried out in four stages: planning, implementation, observation, and reflection. The data sources were obtained from informants (teachers who taught Element 10 of Public Relations and Protocol Management and grade XI MPLB students at SMK N 1 Sukoharjo), documents (teaching modules, student worksheets, student attendance lists, student test scores on creative thinking ability, observations of creative thinking ability, and observations of the implementation of the CPS learning model). Data collection techniques were conducted through tests, observations, and documentation. The validity of the data was tested using expert judgment and triangulation techniques. Data analysis techniques used quantitative data analysis (comparative descriptive) and qualitative data analysis (data reduction, data presentation, and verification). The results showed that the average score of pre-cycle creative thinking ability test was 39,93% with a mastery level of 11,11% categorized as less creative. In the first cycle, the average score of the creative thinking ability test increased to 59.72% with a mastery level of 38.89% categorized as moderately creative, and in the second cycle, the average score of the creative thinking ability test increased to 70,14% with a mastery level of 80,56% categorized as creative. Therefore, it can be concluded that the CPS learning model can improve the creative thinking ability of grade XI MPLB 1 students at SMK N 1 Sukoharjo.